2018
DOI: 10.1097/yct.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Electroconvulsive Therapy in Patients With Implanted Deep Brain Stimulators

Abstract: Currently there is no consensus statement about the safety of electroconvulsive therapy in patients who have implanted electrodes for deep brain stimulation. We present a summary of the existing literature on this topic, consisting of 21 cases, and then report a case performed at the University of Maryland Medical Center. Notably, with appropriate safety precautions and careful patient selection, there were no adverse events reported in the literature that were related to the presence of the deep brain stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Alternatively, there was the postulated risk that exposure of a metallic DBS (or SCS) electrode to the electrical current delivered during ECT could cause heating of the electrode and damage surrounding brain tissue. At least with DBS however, Peroski et al found no case report evidence that ECT caused tissue damage in patients with implanted DBS devices or that DBS was unsafe in this patient group [4]. With respect to ECT's safety in patients with implanted SCS, more research and reporting of adverse events are needed to guide clinical decision-making.…”
Section: To the Editormentioning
confidence: 97%
See 2 more Smart Citations
“…Alternatively, there was the postulated risk that exposure of a metallic DBS (or SCS) electrode to the electrical current delivered during ECT could cause heating of the electrode and damage surrounding brain tissue. At least with DBS however, Peroski et al found no case report evidence that ECT caused tissue damage in patients with implanted DBS devices or that DBS was unsafe in this patient group [4]. With respect to ECT's safety in patients with implanted SCS, more research and reporting of adverse events are needed to guide clinical decision-making.…”
Section: To the Editormentioning
confidence: 97%
“…ECT is an antidepressant intervention which involves the passage of an electrical current through pre-determined electrode configurations placed on the recipient's scalp to induce a seizure. Whilst a recent case report and literature review reported on the safety of ECT in patients with implanted deep brain stimulators (DBS) [4], there is no literature describing the feasibility, safety or efficacy of ECT applied to patients with implanted SCS.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports showed that ECT can be performed-using the MECTA spECTrum 5000 29,30,34,38,41 or Thymatron 3,23,24,26,31,32,35,[37][38][39]41,42 devices-in patients with DBS targeting the subthalamic nucleus, 3,24,26,29,30,32,34,35,38,39,41 the internal globus pallidus, 3,31 or the VIM, 23,25,42 for the treatment of movement disorders. In 1 case, the DBS target for a patient with PD was not specified.…”
Section: Resultsmentioning
confidence: 99%
“…33 When identified by authors, the DBS devices used were the Medtronic system 3,23,26,[29][30][31]34,42 and a rechargeable implantable pulse generator (St Jude Medical, St Paul, Minnesota). 37 Electroconvulsive therapy electrodes can be positioned either bifrontally (BF) 24,27,30,37,38,40,41 or bitemporally (BT), 23,26,28,29,[31][32][33][34][35]39 but a large number of articles indicated placement as far away from the DBS lead insertion point and the connecting cable as possible. Only 1 article provided additional details on the placement of the ECT electrodes: Moscarillo and Annunziata 23 specified that they placed the edge of the ECT electrode 2.5 cm away from the subcutaneous cable of the DBS that ran behind the left ear.…”
Section: Resultsmentioning
confidence: 99%